5(x-3)=2(2x+6)

Simple and best practice solution for 5(x-3)=2(2x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)=2(2x+6) equation:



5(x-3)=2(2x+6)
We move all terms to the left:
5(x-3)-(2(2x+6))=0
We multiply parentheses
5x-(2(2x+6))-15=0
We calculate terms in parentheses: -(2(2x+6)), so:
2(2x+6)
We multiply parentheses
4x+12
Back to the equation:
-(4x+12)
We get rid of parentheses
5x-4x-12-15=0
We add all the numbers together, and all the variables
x-27=0
We move all terms containing x to the left, all other terms to the right
x=27

See similar equations:

| 5(4x/3)=135 | | .06(n-450)=105 | | 70y-6=7 | | 5(11x-)=155 | | f(-3)=-3^2-5(-3)+36 | | 5(11x-)=-28 | | 5x-4=4x-10 | | 3x-11+5x/2=0 | | 6x-3=9x-24 | | 10x=-32-6 | | 7(4x+3)=27x+37 | | 6x-11-7=6(x-3) | | 3−7⋅3+4x=-18 | | 2x+1.9=4.1x+1.27 | | 3.6x-8.4=9.6 | | 2x+2(7-3x)=21 | | F(x)=-2x-5x+7 | | 3x^2+33x-8.1=0 | | 20/13=60/d | | -3x-9=5x+7 | | 12x-48=3x-3 | | 3m+7=97 | | 12x-48=3x-4 | | 7x-4=4x+5= | | x+8/3=x+2/3 | | 7×4=4x+5 | | 2+6x=-2x+10 | | 3x/5+7=2x/6+9 | | 2+6x=2x+10 | | 23=14-7a | | 5(2y-7=3(4y+5) | | 5xx3x-x^2=126 |

Equations solver categories